Early Urdu Journals: A Thematic Study of Poems - Bibi, Naeema; Shahzad, Muhammad Kamran; Hussain, Shah (sourcecoder, 2023)
At the end of the nineteenth century and the beginning of the twentieth century, many Urdu journals were started. Among them are Makhzan, Zamana Dilgadaz, Adib, Ismat, Tahsib al-Nuswan and Ismat etc. The main aim of these journals was to improve society and create awareness and education among women. A variety of articles and reform stories along with many poems were published in these journals. These journals of the 20th century played their role for the reform and development of the society as much as possible. If we look at these poems in the wider context of Urdu poetry, then perhaps these poems will not be seen as having any prominent place, nor do these poems have any significant artistic and intellectual importance. But nevertheless, these poems seem to promote their objectivity. Thematic analysis of these poems has been done in this paper.